2018
DOI: 10.1007/s00383-018-4317-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical implications of serum Mac-2-binding protein (M2BPGi) during regular follow-up of patients with biliary atresia

Abstract: M2BPGi is a novel marker for liver fibrosis in patients with BA. It is especially useful for following patients with BA with a native liver and supporting liver biopsy interpretation findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 21 publications
2
21
0
Order By: Relevance
“…If some noninvasive methods could be uncovered to predict the occurrence of cirrhosis, it enables to prevent the development of liver failure and the need of liver transplantation in BA patients effectively. Three of our included 9 studies found that APRi was a useful noninvasive tool in predicting post-KPE cirrhosis (Grade B, level 2a) [62][63][64]. The sensitivity, speci city and AUC of APRi with different cut-off value in these studies ranged from 71-91%, 81-84% and 0.81 to 0.88, respectively ( Table 3).…”
Section: Biomarkers For Post-kpe Cirrhosismentioning
confidence: 93%
See 4 more Smart Citations
“…If some noninvasive methods could be uncovered to predict the occurrence of cirrhosis, it enables to prevent the development of liver failure and the need of liver transplantation in BA patients effectively. Three of our included 9 studies found that APRi was a useful noninvasive tool in predicting post-KPE cirrhosis (Grade B, level 2a) [62][63][64]. The sensitivity, speci city and AUC of APRi with different cut-off value in these studies ranged from 71-91%, 81-84% and 0.81 to 0.88, respectively ( Table 3).…”
Section: Biomarkers For Post-kpe Cirrhosismentioning
confidence: 93%
“…Original [64] Abbreviations: BA, biliary atresia; MMP-7, matrix metallopeptidase-7; IL-33, interleukin 33; GGT, γ-glutamyl transferase; APRi, aspartate aminotransferase to platelet ratio index; post-KPE, after Kasai portoenterostomy; ELISA, enzyme-linked immunosorbent assay; CLEIA, chemiluminescent enzyme immunoassay. Biomarkers for differentiating BA to non-BA…”
Section: Study Durationmentioning
confidence: 99%
See 3 more Smart Citations